The helicase protein DHX29 promotes translation initiation, cell proliferation, and tumorigenesis - Parsyan, Armen (National Academy of Sciences, 2009)
Translational control plays an important role in cell growth and tumorigenesis. Cap-dependent translation initiation of mammalian mRNAs with structured 5′UTRs requires the DExH-box protein, DHX29, in vitro. Here we show that DHX29 is important for translation in vivo. Down-regulation of DHX29 leads to impaired translation, resulting in disassembly of polysomes and accumulation of mRNA-free 80S monomers. DHX29 depletion also impedes cancer cell growth in culture and in xenografts. Thus, DHX29 is a bona fide translation initiation factor that potentially can be exploited as a target to inhibit cancer cell growth.